Are You Able to Trust Me? Analysis of the Relationships Between Personality Traits and the Assessment of Attractiveness and Trust - Bartosik, Bernadetta; Wojcik, Grzegorz M.; Brzezicka, Aneta; Kawiak, Andrzej (Frontiers in Human Neuroscience, 2021)
Behavioral and neuroimaging studies show that people trust and collaborate with others based on a quick assessment of the facial appearance. Based on the morphological characteristics of the face, i.e. features, shape or colour, it is possible to determine health, attractiveness, trust and some personality traits. The study attempts to indicate the features influencing the perception of attractiveness and trust. In order to select individual factors, a model of backward stepwise logistic regression was used, analyzing the results of the psychological tests and the attractiveness and trust survey. Statistical analysis made it possible to select the most important personality traits related to attractiveness and trust assessments.